The Effect of Accounting Information Technology, Competence and Training on the Quality of Bumdes Financial Statements in Supporting Governance and Tourism Village Development - Muzayyanah; Erie Wardhani, Tri; Setyawati, Yanthi; Tatmimah, Itat; Veronica, Liony (Lembaga Riset Ilmiah, 2025)
This study aims to analyze the influence of accounting information technology, competence, and training on the quality of financial statements of Village-Owned Enterprises (BUMDes) in supporting governance and the development of tourist villages in Dukupuntang District, Cirebon Regency. The novelty of this research lies in the integration of three independent variables that were previously studied separately, now examined simultaneously in relation to the quality of BUMDes financial reporting. This research employs a quantitative approach with an explanatory design. Data were collected through questionnaires distributed to 62 active BUMDes managers in the Dukupuntang area. The data were analyzed using multiple linear regression with the help of SPSS software. The findings indicate that accounting information technology and training do not have a significant influence on the quality of BUMDes financial statements, whereas human resource competence has a positive and significant effect. The conclusion of this study emphasizes the importance of enhancing competence as a key factor in improving the quality of BUMDes financial reports. Theoretically, these findings support stewardship theory and broaden the understanding of competence’s role within public sector accountability systems. Practically, the study implies the need to strengthen the capacity of BUMDes managers through structured and continuous development programs.